Islamic Values in Mottainai Philosophy and Osagari Tradition in Japan - Turistiati, Ade Tuti (IBDA` : Jurnal Kajian Islam dan Budaya, 2019)
Prices of goods in Japan are relatively expensive. Meanwhile, to dispose of used or second hand goods is often difficult even people have to pay for it. The Philosophy of mottainai and osagari tradition are a solution for Japanese people to deal with, so these items are not wasteful. The aim of the study was to analyze Islamic values in the mottainai philosophy and osagari tradition in Japan. This research uses a qualitative approach. Data collection techniques are with observation and indepth interviews of 3 Japanese and 5 Indonesian people living in Japan as research informants. Secondary data were from books, journals, and articles that are relevant to the research theme. The results of this study show that in the tradition of mottainai and osagari, there are Islamic values that benefit human life and protect the environment. Islamic values include preventing wasteful goods with the principles of 3R (Re-use, Reduce, and Recycle) and osagari by giving second hand goods to those who need them. The osagari tradition is a medium of communication, helping each other, and maintaining friendship. The tradition takes place across cultures, which is carried out not only by fellow Japanese, but also Japanese with non-Japanese and even among non-Japanese people living in Japan. Harga barang di Jepang relatif mahal. Sementara itu, membuang barang bekas atau bekas seringkali sulit bahkan orang harus membayarnya. Filsafat tradisi mottainai dan osagari adalah solusi bagi orang Jepang untuk berurusan sehingga barang-barang ini tidak sia-sia. Tujuan dari penelitian ini adalah untuk menganalisis nilai-nilai Islam dalam filsafat mottainai dan tradisi osagari di Jepang. Penelitian ini menggunakan pendekatan kualitatif. Teknik pengumpulan data dengan observasi dan wawancara mendalam terhadap 3 orang Jepang dan 5 orang Indonesia yang tinggal di Jepang sebagai informan penelitian. Data sekunder berasal dari buku, jurnal, dan artikel yang relevan dengan tema penelitian. Hasil penelitian ini menunjukkan bahwa dalam tradisi mottainai dan osagari, ada nilai-nilai Islam yang bermanfaat bagi kehidupan manusia dan melindungi lingkungan. Nilai-nilai Islam termasuk mencegah barangbarang boros dengan prinsip 3R (Re-use, Reduce, and Recycle) dan osagari dengan memberikan barang-barang bekas kepada mereka yang membutuhkannya. Tradisi osagari adalah media komunikasi, saling membantu, dan menjaga persahabatan. Tradisi berlangsung lintas budaya, yang dilakukan tidak hanya oleh sesama Jepang, tetapi juga Jepang dengan non-Jepang dan bahkan di antara orang non-Jepang yang tinggal di Jepang.